Vortex-induced vibration of a 5:1 rectangular cylinder: A comparison of wind tunnel sectional model tests and computational simulations - Nguyen, Dinh Tung; Hargreaves, David M.; Owen, John S. (Elsevier, 2018)
Considered to be representative of a generic bridge deck geometry and characterised by a highly unsteady flow field, the 5:1 rectangular cylinder has been the main case study in a number of studies including the “Benchmark on the Aerodynamics of a Rectangular 5:1 Cylinder” (BARC). There are still a number of limitations in the knowledge of (i) the mechanism of the vortex-induced vibration (VIV) and (ii) of the turbulence-induced effect for this particular geometry. Extended computational and wind tunnel studies were therefore conducted by the authors to address these issues. This paper primarily describes wind tunnel and computational studies using a sectional model in an attempt to bring more insight into Point (i). By analysing the distribution and correlation of the surface pressure around an elastically mounted 5:1 rectangular cylinders in smooth and turbulent flow, it revealed that the VIV was triggered by the motion-induced leading-edge vortex; a strongly correlated flow feature close to the trailing edge was then responsible for an increase in the structural response.